Optimization of TIG welding parameters for 6061Al alloy using Taguchi's design of experiments. (2018) - Jayashree, P.K.; Sharma, S.S.; Shetty, Raviraj; Mahato, Ashish; Gowrishankar, M.C.
Abstract: Aluminium in pure form has comparably less strength, though some of its alloys are stronger than structural steels. 6061Al alloy is so strong and hence used in aggressive conditions like aerospace applications. Possessing these superior properties, the defects like porosity, hot cracking and stress corrosion cracking during welding of aluminium alloy is yet to be optimized. This paper focus to determine the favourable welding conditions for Tungsten Inert Gas (TIG) welding of 6061Al alloy based on Taguchi's design of experiments. Hence the concentration is on experimentally identifying the effect of the different welding parameters on hardness and weld bead geometry at weld zone under different welding condition obtained by L9 Orthogonal array using Taguchi's design of experiments